2022
DOI: 10.3390/ijerph192214906
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Complexity: Challenges to Implementing Community-Led Nature-Based Solutions in England Pre- and Post-COVID-19

Abstract: Nature-based solutions (NbS), including green social prescribing (GSP), are sustainable ways to address health and wellbeing, especially since the COVID-19 pandemic exacerbated the strain on healthcare. NbS require national and local cross-sector coordination across complex, interrelated systems, but little is known about the specific challenges this poses for community-led NbS. We carried out a traditional literature review to establish the context and knowledge base for this study and interviewed 26 stakehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…Additionally, there is widespread consensus regarding the lack of awareness concerning the effectiveness and cost of nature-based solutions (which can include nature-based health interventions) among the general public and key stakeholders, including service users and healthcare professionals. Issues of sporadic and unsustainable funding, leading to a dependence on continuity and volunteer capacity, as well as challenges in offering and maintaining urban green spaces and access to protected areas, are highlighted [53].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is widespread consensus regarding the lack of awareness concerning the effectiveness and cost of nature-based solutions (which can include nature-based health interventions) among the general public and key stakeholders, including service users and healthcare professionals. Issues of sporadic and unsustainable funding, leading to a dependence on continuity and volunteer capacity, as well as challenges in offering and maintaining urban green spaces and access to protected areas, are highlighted [53].…”
Section: Discussionmentioning
confidence: 99%
“…Different types of naturebased interventions have been examined, including community gardening [48,49], bluecare or water-based activities [50,51], and general outdoor activities [52]. Some studies in particular explore GSP in the context of COVID-19 [53,54]. These studies have identified a range of challenges and opportunities for research and practice.…”
Section: Nature-based Servicesmentioning
confidence: 99%
“…One of these is the lack of convincing evidence that the benefit from nature and community assets can be realised through GSP [57,58]. Another important consideration is the lack of consistent or standardised referral mechanisms, as schemes are funded, structured, and delivered diversely [53], and so the referral process is highly individual [54].…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations